2013 IEEE International Conference on Robotics and Automation 2013
DOI: 10.1109/icra.2013.6631192
|View full text |Cite
|
Sign up to set email alerts
|

Human-robot cooperative object swinging

Abstract: Abstract-This paper investigates goal-directed cooperative object swinging as a novel physical human-robot interaction scenario. We develop an energy-based control concept, which enables a robot to cooperate with a human in a goal-directed swing-up task. The robot can be assigned to be a leader or an actively contributing follower. We conduct a virtual reality experiment to compare effort sharing and performance of mixed human-human and human-robot dyads. The leader and the follower controllers yield similar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The human interacts with the virtual reality through a haptic device. The setup is explained in detail in [17]. The trapezoidal pendulum is identical to that of the simulation based experiment of this section.…”
Section: A Trapezoidal Pendulum Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human interacts with the virtual reality through a haptic device. The setup is explained in detail in [17]. The trapezoidal pendulum is identical to that of the simulation based experiment of this section.…”
Section: A Trapezoidal Pendulum Experimentsmentioning
confidence: 99%
“…In our previous works [17], [18], human-robot object swinging is motivated by the extension of the manipulation capabilities with respect to bulky, flexible objects. Our exemplary task is cooperative swinging of a sports mat in order to lift it onto a trolley.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A virtual reality experiment showed that the robotic leader and follower yield similar results compared to their human counterparts. In this paper, the control concept of [8] is extended to allow cooperative swing-up of more complex pendulum-like objects that can oscillate in several modes (see Fig. 1(c)).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows an illustration of flexible object swinging (b) as a combination of two extremes: an oscillating entity formed by the partners' arms and a rigid object (a) and a pendulum-like object that can oscillate itself (c). In [8], we investigated goal-directed cooperative swinging of a simple v-shaped pendulum with a point mass in contrast to the cylindrical mass displayed in Fig. 1(c).…”
Section: Introductionmentioning
confidence: 99%